Is Persistent Post-COVID Headache Associated With Protein-Protein Interactions Between Antibodies Against Viral Spike Protein and CGRP Receptor?: A Case Report - Özkan, Esra; Celebi, Özlem; Keskin, Özlem; Gursoy, Attila; Gürsoy-Özdemir, Yasemin (Frontiers in Pain Research, 2022)
Background After the acute pandemic of coronavirus disease 2019 (COVID-19), a wide variety of symptoms are identified under the term post-COVID syndrome, such as persistent headache. Post-COVID headache can be presented in a broad spectrum like headache attributed to systemic infection, chronification of already existing primary headache, or long-lasting, and also late-onset new daily persistent headache. Still, little is known about the pathophysiology of post-COVID headache, but activation of the trigeminovascular system may be one of the players. Case Report Here, we present a case with a severe, long-lasting post-COVID headache and its sudden cessation with calcitonin gene-related peptide (CGRP) monoclonal antibody treatment. Conclusion In our previous protein mimicry study, we have pointed at mimicry of virus spike protein and CGRP receptors. This mechanism may enlighten the current, common, and yet unsolved post-COVID headache cases.